A local instrumental estimation method for generalized additive volatility models - Woocheol Kim; Oliver Linton (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
We investigate a new separable nonparametric model for time series, which includes many ARCH models and AR models already discussed in the literature. We also propose a new estimation procedure based on a localization of the econometric method of instrumental variables. Our method has considerable computational advantages over the competing marginal integration or projection method.
urn:nbn:de:kobv:11-10048128
Keywords: 330